Konflik Bioetika dalam Fenomena Adu Ayam: Analisis Kesejahteraan Hewan dan Nilai Etik Lokal - Rohim Rohim; Mohammad Haris Musthofa; Irpan Noerdin; Tri Cahyanto (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The phenomenon of cockfighting still persists in various communities in Indonesia as a cultural practice, entertainment, and symbol of certain social identities. However, this practice raises serious issues when analyzed from the perspectives of modern bioethics, animal welfare, public health, and normative religious values, particularly maqāṣid al-sharī‘ah. This study aims to examine the ethical conflicts that arise from cockfighting by analyzing the biological and physiological impacts on animals, violations of animal welfare principles, and tensions between local cultural legitimacy and universal ethical standards. This research uses a descriptive-qualitative approach based on a review of relevant scientific literature, including national and international publications in the fields of bioethics, animal welfare, animal health, and law. The results of the study show that cockfighting systematically causes severe physical injury, extreme biological stress, behavioral disorders, and an increased risk of zoonotic disease transmission, so it can be categorized as a form of organized animal cruelty. From a bioethical and maqāṣid al-sharī‘ah perspective, this practice contradicts the principles of respect for life, non-maleficence, and protection of life and public welfare. The lack of legal protection focused on animal welfare reinforces the urgency of a transformative approach through regulatory reformulation, public education, and the development of non-violent cultural alternatives. This study is expected to serve as a scientific and ethical basis for policy formulation and contextual and sustainable animal protection efforts.